Atypical pit craters on Mars: New insights from THEMIS, CTX, and HiRISE observations. Issue 6 (3rd June 2015) - Cushing, Glen E.; Okubo, Chris H.; Titus, Timothy N.
Abstract More than 100 pit craters in the Tharsis region of Mars exhibit morphologies, diameters, and thermal behaviors that diverge from the much larger bowl‐shaped pit craters that occur in most regions across Mars. These Atypical Pit Craters (APCs) generally have sharp and distinct rims, vertical or overhanging walls that extend down to their floors, surface diameters of 50–350 m, and high depth to diameter (d/D) ratios that are usually greater than 0.3 (which is an upper range value for impacts and bowl‐shaped pit craters) and can exceed values of 1.8. Observations by the Mars Odyssey Thermal Emission Imaging System (THEMIS) show that APC floor temperatures are warmer at night and fluctuate with much lower diurnal amplitudes than nearby surfaces or adjacent bowl‐shaped pit craters. Kīlauea volcano, Hawai'i, hosts pit craters that formed through subsurface collapse into active volcanic dikes, resulting in pits that can appear morphologically analogous to either APCs or bowl‐shaped pit craters. Partially drained dikes are sometimes exposed within the lower walls and floors of these terrestrial APC analogs and can form extensive cave systems with unique microclimates. Similar caves in Martian pit craters are of great interest for astrobiology. This study uses new observations by the Mars Reconnaissance Orbiter High Resolution Imaging Science Experiment (HiRISE) and Context Camera to refine previous work where seven APCs were described from lower resolution THEMIS visible wavelength observations. Here we identify locations of 115 APCs, map their distribution across the Tharsis region, characterize their internal morphologies with high‐resolution observations, and discuss possible formation mechanisms.